A platonic solid templating Archimedean solid: an unprecedented nanometre-sized Ag37 cluster1. Issue 18 (14th May 2015) - Li, Xiao-Yu; Su, Hai-Feng; Yu, Kai; Tan, Yuan-Zhi; Wang, Xing-Po; Zhao, Ya-Qin; Sun, Di; Zheng, Lan-Sun
<x xml:space="preserve">Abstract</x> A platonic tetrahedron templated Archimedean truncated tetrahedron – an unprecedented nanometre-sized Ag37 cluster.